Pengaruh komitmen, budaya organisasi, dan kepuasan kerja terhadap organization citizenship behavior - Suhery, Suhery; Sutiyem, Sutiyem (Jurnal Kajian Manajemen Bisnis, 2018)
Organizational Culture on Organizational Citizenship Behavior; 3) determine the effect of job satisfaction on Organization Citizenship Behavior and; 4) determine the effect of Organizational Commitment, Organizational Culture, and Job Satisfaction with the Organization Citizenship Behavior. The research sample consisted of 35 respondents. Data collection was performed using a questionnaire, after which a validity and reliability test was performed using SPSS Software. The data analysis technique is done by multiple linear regression analysis, the results of the study show: 1) organizational commitment has a positive and significant effect on Organization Citizenship Behavior; 2) organizational Culture has a positive and significant effect on Organization Citizenship Behavior, 3) job satisfaction has a positive and significant effect on Organization Citizenship Behavior and; 4)organizational commitment, organizational culture, and job satisfaction have a positive and significant impact on Organization Citizenship Behavior.Keywords: Organizational commitment; organizational culture; job satisfaction; organizational citizenship behavior (OCB).